A mixed acid-based full vanadium redox flow battery electrolyte containing a bismuth-based additive, a preparation method and applications
Patent Information
- Application Number
- CN202610553598.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-24
- Publication Date
- 2026-06-26
Smart Images

Figure CN122291609A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery electrolyte technology, specifically to a mixed acid-based vanadium redox flow battery electrolyte containing bismuth additives, its preparation method, and its application. Background Technology
[0002] Vanadium redox flow batteries (VRBs) are characterized by long cycle life, high safety, and independent design of power and capacity, making them an important technological route in large-scale electrochemical energy storage. They have broad application prospects in grid peak shaving, new energy grid connection, and distributed energy storage systems. Existing VRBs mostly use pure sulfuric acid electrolytes, but the solubility of vanadium ions is low, and hydrolysis, polymerization, and precipitation easily occur under high concentration conditions, limiting battery energy density and resulting in insufficient long-term operational stability. To improve the concentration and stability of vanadium electrolytes, a mixed acid system of sulfuric acid and hydrochloric acid is usually used. This utilizes the coordination effect of chloride ions on vanadium ions to improve vanadium ion solubility and broaden the applicable concentration and temperature range of the electrolyte. However, the mixed acid system has significant drawbacks in practical applications: when the positive electrode is charged to a high potential range, free chloride ions in the electrolyte are easily electrochemically oxidized to generate chlorine gas. This not only causes electrolyte component loss and reduces battery charge and discharge efficiency but also corrodes electrodes, pipelines, and membrane components, affecting battery life and operational safety. Simultaneously, the negative electrode V³ + / V² + The slow reaction kinetics of the redox couple and the significant hydrogen evolution side reaction further restrict the improvement of the overall battery performance.
[0003] To address the aforementioned issues, existing technologies attempt to regulate the performance of electrolytes in mixed acid systems using electrolyte additives. However, most reported additives have a single function and cannot adequately address the inherent problems of mixed acid electrolyte systems, such as chlorine suppression at the positive electrode, catalysis at the negative electrode, and vanadium ion stabilization. More importantly, in current flow battery stack technology, conventional stacks only add catalysts to one side. When capacity decay occurs during battery operation and capacity recovery is required, it is impossible to directly achieve capacity recovery by mixing the positive and negative electrolytes within the stack. Otherwise, the electrolyte on the side without catalyst would be contaminated, thus affecting the overall battery performance. Summary of the Invention
[0004] This invention addresses the problems existing in the prior art by providing a mixed acid-based vanadium redox flow battery electrolyte containing bismuth additives, its preparation method, and its application.
[0005] The technical solution adopted in this invention is: a mixed acid-based vanadium redox flow battery electrolyte containing bismuth additives. The desired modified battery electrolyte can be obtained by adding bismuth additives to the mixed acid-based vanadium redox flow battery electrolyte and then electrolyzing it. The concentration of the bismuth-containing additive in the modified battery electrolyte is 0.01 mol / L – 0.1 mol / L; the bismuth-containing additive is one or more of bismuth sulfate, bismuth formate, bismuth citrate, and bismuth tartrate mixed in any proportion.
[0006] Furthermore, the vanadium ions in the mixed acid-based vanadium redox flow battery electrolyte are tetravalent vanadium ions, with a concentration of 1.6 mol / L-2.5 mol / L.
[0007] Furthermore, the sulfate concentration in the mixed acid-based vanadium redox flow battery electrolyte is 3 mol / L-6 mol / L, and the chloride ion concentration in the modified battery electrolyte is 0.5 mol / L-2.5 mol / L.
[0008] A method for preparing a mixed-acid-based all-vanadium redox flow battery electrolyte containing bismuth additives includes the following steps: Step 1: Prepare a tetravalent vanadium oxysulfate solution; Step 2: Add the bismuth-containing additive and hydrochloric acid to the vanadium oxysulfate solution obtained in Step 1, stir thoroughly to react, and then electrolyze to obtain the desired modified battery electrolyte.
[0009] Furthermore, the method for preparing the tetravalent vanadium oxysulfate solution is as follows: Under oil bath conditions, adding oxalic acid to a sulfuric acid solution to reduce vanadium pentoxide yields a tetravalent vanadium oxysulfate solution.
[0010] Furthermore, the oil bath temperature is 60-80 ℃.
[0011] Furthermore, in step 2, the reaction temperature is 50-70 ℃ and the reaction time is 1-3 h.
[0012] Application of a bismuth-based mixed-acid vanadium redox flow battery electrolyte, wherein the modified battery electrolyte is used to assemble a mixed-acid vanadium redox flow battery.
[0013] A mixed-acid-based vanadium redox flow battery containing bismuth additives, wherein the battery is assembled using a modified battery electrolyte as the positive and negative electrode electrolytes.
[0014] The beneficial effects of this invention are: The bismuth-containing additive mixed acid-based vanadium redox flow battery electrolyte obtained by this invention is simultaneously applied to the electrolytes on both the positive and negative electrodes, so that the positive and negative electrode electrolyte systems can maintain compatibility. Therefore, when the battery is undergoing capacity recovery, the positive and negative electrode electrolytes can be directly mixed to achieve a rebalancing of electrolyte concentration and volume, which has the outstanding advantage of efficient capacity recovery.
[0015] The bismuth-containing additive mixed acid-based vanadium redox flow battery electrolyte obtained by this invention can be applied to both the positive and negative electrodes of the electrolyte. In the mixed acid-based electrolyte, it plays a triple synergistic role in inhibiting chlorine in the positive electrode, catalyzing in the negative electrode, and stabilizing vanadium ions at high temperature. This significantly improves the redox reaction kinetic rate and electrochemical reversibility during battery cycling, thereby achieving long-term stable operation of the battery. Attached Figure Description
[0016] Figure 1 The comparison curves of cyclic voltammetry tests of the electrolyte obtained in Example 1 of this invention and the blank control group are shown.
[0017] Figure 2 The figure shows the comparison curves of the electrolyte obtained in Example 1 of this invention and the blank control group under high temperature (40 °C) cyclic voltammetry test.
[0018] Figure 3 The image shows the vanadium ion precipitation of the mixed acid-based vanadium redox flow battery electrolyte obtained in Example 1 of this invention and the blank control group after being kept at 40 degrees Celsius for 48 hours.
[0019] Figure 4 The image shows the SEM image of the negative electrode in the electrolyte test obtained in Example 1 of this invention and the blank control group.
[0020] Figure 5 This is a battery cycle performance diagram obtained in Example 1 of the present invention.
[0021] Figure 6 This is the battery capacity recovery curve obtained in Example 1 of the present invention.
[0022] Figure 7 The comparison curves of cyclic voltammetry tests of the electrolyte obtained in Example 2 of this invention and the blank control group are shown.
[0023] Figure 8 The comparison curves of the electrolyte obtained in Example 2 of this invention and the blank control group are shown in the high temperature (40 °C) cyclic voltammetry test curves.
[0024] Figure 9 The image shows the vanadium ion precipitation of the mixed acid-based vanadium redox flow battery electrolyte obtained in Example 2 of this invention and the blank control group after being kept at 40 degrees Celsius for 48 hours.
[0025] Figure 10 The image shows the SEM image of the negative electrode in the electrolyte test obtained in Example 2 of this invention and the blank control group.
[0026] Figure 11 This is a battery cycle performance diagram obtained in Example 2 of the present invention.
[0027] Figure 12 This is the battery capacity recovery curve obtained in Example 2 of the present invention.
[0028] Figure 13 The comparison curves of cyclic voltammetry tests of the electrolyte obtained in Example 3 of this invention and the blank control group are shown.
[0029] Figure 14 The comparison curves of the electrolyte obtained in Example 3 of this invention and the blank control group are shown in the high temperature (40 °C) cyclic voltammetry test curves.
[0030] Figure 15 The image shows the vanadium ion precipitation of the mixed acid-based vanadium redox flow battery electrolyte obtained in Example 3 of this invention and the blank control group after being kept at 40 degrees Celsius for 48 hours.
[0031] Figure 16 This is a SEM image of the negative electrode in the electrolyte test obtained in Example 3 of the present invention.
[0032] Figure 17 This is a battery cycle performance diagram obtained in Example 3 of the present invention.
[0033] Figure 18 This is the battery capacity recovery curve obtained in Example 3 of the present invention.
[0034] Figure 19 This is a comparison curve of the cyclic voltammetry test of the electrolyte obtained in Example 4 of the present invention and the blank control group.
[0035] Figure 20 The comparison curves of the electrolyte obtained in Example 4 of this invention and the blank control group are shown in the high temperature (40 °C) cyclic voltammetry test curves.
[0036] Figure 21 The image shows the vanadium ion precipitation of the mixed acid-based vanadium redox flow battery electrolyte obtained in Example 4 of this invention and the blank control group after being kept at 40 degrees Celsius for 48 hours.
[0037] Figure 22 The image shows the SEM image of the negative electrode in the electrolyte test obtained in Example 4 of this invention and the blank control group.
[0038] Figure 23 This is a battery cycle performance diagram obtained in Example 4 of the present invention.
[0039] Figure 24 This is the battery capacity recovery curve obtained in Example 4 of the present invention.
[0040] Figure 25 The cyclic voltammetry test curve of the electrolyte obtained in the comparative example of this invention is shown.
[0041] Figure 26 The high-temperature (40 °C) cyclic voltammetry test curve of the electrolyte obtained as a comparative example of this invention is shown.
[0042] Figure 27This is a SEM image of the negative electrode obtained in the electrolyte test of the comparative example of this invention.
[0043] Figure 28 This is a battery cycle performance diagram obtained as a comparative example of the present invention.
[0044] Figure 29 This is a battery capacity recovery curve obtained as a comparative example of the present invention. Detailed Implementation
[0045] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0046] A mixed-acid-based vanadium redox flow battery electrolyte containing bismuth additives is obtained by adding bismuth additives to the mixed-acid-based vanadium redox flow battery electrolyte and then electrolyzing it to obtain the desired modified battery electrolyte. The concentration of the bismuth-containing additive in the modified battery electrolyte is 0.01 mol / L – 0.1 mol / L; the bismuth-containing additive is one or more of bismuth sulfate, bismuth formate, bismuth citrate, and bismuth tartrate mixed in any proportion.
[0047] The mixed-acid vanadium redox flow battery electrolyte (this electrolyte is the mixed-acid vanadium redox flow battery electrolyte used before the addition of bismuth additive) contains tetravalent vanadium ions at a concentration of 1.6 mol / L–2.5 mol / L. The sulfate concentration in the mixed-acid vanadium redox flow battery electrolyte is 3 mol / L–6 mol / L, and the chloride concentration in the modified battery electrolyte is 0.5 mol / L–2.5 mol / L.
[0048] A method for preparing a mixed-acid-based all-vanadium redox flow battery electrolyte containing bismuth additives includes the following steps: Step 1: Prepare a tetravalent vanadium oxysulfate solution; the preparation method for the tetravalent vanadium oxysulfate solution is as follows: Vanadium pentoxide solution is obtained by reducing it with oxalic acid (add oxalic acid as needed) in a sulfuric acid solution under oil bath conditions. The oil bath temperature is 60-80 ℃. The reaction temperature is 50-70 ℃, and the reaction time is 1-3 h.
[0049] Step 2: Add the bismuth-containing additive and hydrochloric acid to the vanadium oxysulfate solution obtained in Step 1, stir thoroughly to react, and then electrolyze to obtain the desired modified battery electrolyte.
[0050] Example 1 A method for preparing a mixed-acid-based all-vanadium redox flow battery electrolyte containing bismuth additives includes the following steps: Step 1: Under 70 ℃ oil bath conditions, oxalic acid is added to a 4.5 mol / L sulfuric acid solution to reduce vanadium pentoxide, thus obtaining the desired tetravalent vanadium oxysulfate solution. Vanadium pentoxide is added at a concentration of 1.15 mol / L.
[0051] Step 2: Add bismuth sulfate and hydrochloric acid to the vanadium oxysulfate solution obtained in Step 1, stir magnetically at 60 °C for 2 h, and then electrolyze to obtain the desired modified battery electrolyte; bismuth sulfate is added at a concentration of 0.07 mol / L and hydrochloric acid is added at a concentration of 1.7 mol / L in the modified battery electrolyte.
[0052] To illustrate the effects of the present invention, a blank control group was set up. The remaining steps of the blank control group were the same as those in Example 1, except that step 2 did not include bismuth sulfate.
[0053] Batteries were assembled using electrolytes obtained from the modified battery electrolyte group and the blank control group, and battery performance was tested.
[0054] Cyclic Voltmeter-Ampere Test: A three-electrode system was used: working electrode: platinum-carbon electrode; counter electrode: graphite electrode; reference electrode: saturated calomel electrode; scanning range: 0.4 V. 1.4 V, scan rate 30 mV / s.
[0055] Figure 1 The figures show the cyclic voltammetry test results of the electrolyte obtained in Example 1 of this invention and the blank control group (the dashed line represents the blank control group, and the solid line represents the results of Example 1). As can be seen from the figure, under the same scan rate, the electrolyte of Example 1 has a higher peak response current during the redox reaction, and there is no obvious characteristic peak corresponding to chlorine gas evolution at a higher potential, indicating that the bismuth-containing additive can effectively suppress the chlorine evolution phenomenon of the electrolyte on the positive electrode side.
[0056] Figure 2 The figure shows the high-temperature cyclic voltammetry test results of the electrolyte obtained in Example 1 of this invention and the blank control group (the dashed line is the blank control group, and the solid line is the result of Example 1, which was tested at 40 °C). As can be seen from the figure, the electrolyte in Example 1 also did not have obvious chlorine gas evolution characteristic peaks at high temperature, which proves that the bismuth-containing additive releases some chloride ions to participate in the positive electrode reaction at high temperature, effectively inhibiting the evolution of vanadium ions.
[0057] Figure 3 Images show the vanadium ion precipitation in the modified battery electrolytes obtained in Example 1 and the blank control group (left image is the blank control group, right image is the modified battery electrolyte obtained in Example 1) after being kept at 40 degrees Celsius for 48 h. As can be seen from the images, no obvious precipitation occurred in the electrolyte of Example 1, indicating that [BiCl] in the electrolyte... n ](3-n)+ The complex dissociates, and the free chloride ions further enhance the solubility stability of vanadium ions in the electrolyte.
[0058] Figure 4 The image shows the SEM image of the negative electrode after cyclic voltammetry testing of the electrolyte in Example 1 of this invention. As can be seen from the image, bismuth ions in the bismuth-containing additive are reduced to elemental bismuth in situ under the influence of the flow field and electric field and adhere to the electrode surface, which accelerates the electrochemical reaction kinetics of vanadium ions in the negative electrode and inhibits the hydrogen evolution reaction.
[0059] Battery performance testing conditions: at 200 mA / cm 2 Under a current density, cyclic charging and discharging were performed, with a charging cutoff voltage of 1.55 V and a discharging cutoff voltage of 0.8 V. Both the positive and negative electrodes used 50 mL of modified battery electrolyte.
[0060] The modified battery electrolyte obtained in this embodiment was used to assemble a battery for performance testing, and the results are as follows: Figure 5 As shown in the figure, after 150 cycles, the battery achieved a coulombic efficiency of 97.89%, an energy efficiency of 80.33%, and a voltage efficiency of 82.07%, representing improvements of 2.55%, 9.75%, and 8.04% respectively compared to the control group.
[0061] The capacity recovery curve of the battery assembled with the modified battery electrolyte obtained in this embodiment is as follows: Figure 6 As shown in the figure, after 300 charge-discharge cycles, the capacity retention rate can reach 85.4%. At this time, the positive and negative electrolytes are fully mixed and then constant current charge-discharge test is performed. The discharge capacity can be restored to 98.5% of the initial discharge capacity.
[0062] Example 2 A method for preparing a mixed-acid-based all-vanadium redox flow battery electrolyte containing bismuth additives includes the following steps: Step 1: Under 60 ℃ oil bath conditions, oxalic acid is added to a 3 mol / L sulfuric acid solution to reduce vanadium pentoxide, thus obtaining the desired tetravalent vanadium oxysulfate solution. Vanadium pentoxide is added at a concentration of 0.8 mol / L.
[0063] Step 2: Add bismuth formate and hydrochloric acid to the vanadium oxysulfate solution obtained in Step 1, stir magnetically for 1 h at 50 ℃, and then electrolyze to obtain the desired modified battery electrolyte; add bismuth formate at a concentration of 0.05 mol / L and hydrochloric acid at a concentration of 0.5 mol / L in the modified battery electrolyte.
[0064] To illustrate the effects of the present invention, a blank control group was set up. The remaining steps of the blank control group were the same as those in Example 1, except that step 2 did not include bismuth formate.
[0065] Batteries were assembled using electrolytes obtained from the modified battery electrolyte group and the blank control group, and battery performance was tested.
[0066] The cyclic voltammetry test method is as described in Example 1, and the battery performance test method is as described in Example 1.
[0067] Figure 7 The figures show the positive electrode cyclic voltammetry test curves of the electrolytes obtained in Example 2 and the blank control group (solid line represents the result of Example 2, dashed line represents the result of the blank control group). It can be seen from the figure that, at the same scan rate, the electrolyte of Example 2 has a higher peak response current during the redox reaction, and there is no obvious characteristic peak corresponding to chlorine evolution at a higher potential, which proves that the bismuth-containing additive can effectively suppress the chlorine evolution phenomenon of the electrolyte on the positive electrode side.
[0068] Figure 8 The figure shows the high-temperature cyclic voltammetry test results of the electrolyte obtained in Example 2 of this invention and the blank control group (the dashed line is the blank control group, and the solid line is the result of Example 2, which was tested at 40 °C). As can be seen from the figure, the electrolyte in Example 2 also did not have obvious chlorine gas evolution characteristic peaks at high temperature, which proves that the bismuth-containing additive releases some chloride ions to participate in the positive electrode reaction at high temperature, effectively inhibiting the evolution of vanadium ions.
[0069] Figure 9 Images show the vanadium ion precipitation in the battery electrolytes obtained in Example 2 (right side) and the blank control group (left side) after being incubated at 40°C for 48 h. It can be seen that no obvious precipitation occurred in the electrolyte of Example 2, indicating that [BiCl] in the electrolyte... n ] (3-n)+ The complex dissociates, and the free chloride ions further enhance the solubility stability of vanadium ions in the electrolyte.
[0070] Figure 10 The image shows a SEM image of the negative electrode after performance testing in Example 2. It can be seen from the image that bismuth ions in the bismuth-containing additive are reduced to elemental bismuth in situ under the action of the flow field and electric field and adhere to the electrode surface, which accelerates the electrochemical reaction kinetics of vanadium ions in the negative electrode and inhibits the hydrogen evolution reaction.
[0071] Figure 11 The battery performance test results obtained in Example 2 show that after 150 cycles, the coulombic efficiency reached 97.02%, the energy efficiency reached 76.49%, and the voltage efficiency reached 78.84%, which were 1.68%, 5.91%, and 4.81% higher than the blank control group, respectively.
[0072] Figure 12 The capacity recovery curve of the battery obtained in Example 2 shows that after 300 charge-discharge cycles, the capacity retention rate can reach 77.9%. At this time, the positive and negative electrolytes are fully mixed and then constant current charge-discharge test is performed. The discharge capacity can be restored to 96.38% of the initial discharge capacity.
[0073] Example 3 A method for preparing a mixed-acid-based all-vanadium redox flow battery electrolyte containing bismuth additives includes the following steps: Step 1: Under 80 ℃ oil bath conditions, oxalic acid is added to a 6 mol / L sulfuric acid solution to reduce vanadium pentoxide, thus obtaining the desired tetravalent vanadium oxysulfate solution. Vanadium pentoxide is added at a concentration of 1.25 mol / L.
[0074] Step 2: Add bismuth citrate and hydrochloric acid to the vanadium oxysulfate solution obtained in Step 1, and stir magnetically for 3 h at 70 ℃. Then electrolyze to obtain the desired modified battery electrolyte. Bismuth citrate is added at a concentration of 0.1 mol / L and hydrochloric acid is added at a concentration of 2.5 mol / L in the modified battery electrolyte.
[0075] To illustrate the effects of the present invention, a blank control group was set up. The remaining steps of the blank control group were the same as those in Example 1, except that step 2 did not include bismuth citrate.
[0076] Batteries were assembled using electrolytes obtained from the modified battery electrolyte group and the blank control group, and battery performance was tested.
[0077] The cyclic voltammetry test method is as described in Example 1, and the battery performance test method is as described in Example 1.
[0078] Figure 13 The figures show the cyclic voltammetry curves of the positive electrode electrolytes obtained in Example 3 and the blank control group (solid line represents the results of Example 3, dashed line represents the results of the blank control group). As can be seen from the figures, at the same scan rate, the electrolyte in Example 3 exhibits a higher peak response current during the redox reaction, and there is no obvious characteristic peak corresponding to chlorine evolution at a higher potential, proving that the bismuth-containing additive can effectively suppress chlorine evolution in the positive electrode electrolyte.
[0079] Figure 14 The figure shows the high-temperature cyclic voltammetry test results of the electrolyte obtained in Example 3 of this invention and the blank control group (the dashed line is the blank control group, and the solid line is the result of Example 3, which was tested at 40 °C). As can be seen from the figure, the electrolyte in Example 3 also did not have obvious chlorine gas evolution characteristic peaks at high temperature, which proves that the bismuth-containing additive releases some chloride ions to participate in the positive electrode reaction at high temperature, effectively inhibiting the evolution of vanadium ions.
[0080] Figure 15 Images show the vanadium ion precipitation in Example 3 (right side) and the blank control group (left side) after incubation at 40°C for 48 h. It can be seen that no obvious precipitate was formed in the electrolyte of Example 3, indicating that [BiCl] in the electrolyte... n ] (3-n)+ The complex dissociates, and the free chloride ions further enhance the solubility stability of vanadium ions in the electrolyte.
[0081] Figure 16 The image shows the SEM image of the negative electrode in the electrolyte test of Example 3. It can be seen from the image that bismuth ions in the bismuth-containing additive are reduced to elemental bismuth in situ under the action of the flow field and electric field and adhere to the electrode surface, which accelerates the electrochemical reaction kinetics of vanadium ions in the negative electrode and inhibits the hydrogen evolution reaction.
[0082] The electrolyte obtained in Example 3 was used to assemble a battery, and battery performance was tested. The results are as follows: Figure 17 As shown in the figure, after 150 cycles, the coulombic efficiency reached 96.97%, the energy efficiency reached 77.07%, and the voltage efficiency reached 79.48%, which were 1.63%, 6.49%, and 5.45% higher than the blank control group, respectively.
[0083] Battery capacity recovery curve as shown Figure 18 As shown in the figure, after 300 charge-discharge cycles, the capacity retention rate can reach 73.8%. At this time, the positive and negative electrolytes are fully mixed and then constant current charge-discharge test is performed. The discharge capacity can be restored to 95.71% of the initial discharge capacity.
[0084] Example 4 A method for preparing a mixed-acid-based all-vanadium redox flow battery electrolyte containing bismuth additives includes the following steps: Step 1: Under 70 ℃ oil bath conditions, oxalic acid is added to a 4.2 mol / L sulfuric acid solution to reduce vanadium pentoxide, thus obtaining the desired tetravalent vanadium oxysulfate solution. Vanadium pentoxide is added at a concentration of 1 mol / L.
[0085] Step 2: Add bismuth tartrate and hydrochloric acid to the vanadium oxysulfate solution obtained in Step 1, stir magnetically at 60 °C for 2 h, and then electrolyze to obtain the desired modified battery electrolyte; add bismuth tartrate at a concentration of 0.01 mol / L and hydrochloric acid at a concentration of 2 mol / L in the modified battery electrolyte.
[0086] To illustrate the effects of the present invention, a blank control group was set up. The remaining steps of the blank control group were the same as those in Example 1, except that step 2 did not include bismuth tartrate.
[0087] Batteries were assembled using electrolytes obtained from the modified battery electrolyte group and the blank control group, and battery performance was tested.
[0088] The cyclic voltammetry test method is as described in Example 1, and the battery performance test method is as described in Example 1.
[0089] The cyclic voltammetry curves of the positive electrode of the electrolyte obtained in Example 4 and the blank control group are as follows: Figure 19 As shown in the figure (solid line represents the results of Example 4, dashed line represents the results of the blank control group), it can be seen from the figure that under the same scan rate, the electrolyte of Example 4 has a higher peak response current during the redox reaction, and there is no obvious characteristic peak corresponding to chlorine gas evolution at a higher potential, which proves that the bismuth-containing additive can effectively suppress the chlorine evolution phenomenon of the electrolyte on the positive electrode side.
[0090] Figure 20 The figure shows the high-temperature cyclic voltammetry test results of the electrolyte obtained in Example 4 of this invention and the blank control group (the dashed line represents the blank control group, and the solid line represents the results of Example 4, which were obtained at 40 °C). As can be seen from the figure, the electrolyte in Example 4 also did not have obvious chlorine gas evolution characteristic peaks at high temperatures, proving that the bismuth-containing additive releases some chloride ions at high temperatures to participate in the positive electrode reaction, effectively suppressing the evolution of vanadium ions.
[0091] The vanadium ion deposition in the electrolyte after incubation at 40°C for 48 h in Example 4 (right side) and the blank control group (left side) are shown in the figure. Figure 21 As shown, it can be seen that no obvious precipitate was formed in the electrolyte of Example 4, indicating that [BiCl] in the electrolyte... n ] (3-n)+ The complex dissociates, and the free chloride ions further enhance the solubility stability of vanadium ions in the electrolyte.
[0092] The SEM image of the negative electrode after testing the electrolyte obtained in Example 4 is shown below. Figure 22 As shown in the figure, bismuth ions in the bismuth-containing additive are reduced to elemental bismuth in situ under the influence of the flow field and electric field and adhere to the electrode surface, which accelerates the electrochemical reaction kinetics of vanadium ions at the negative electrode and inhibits the hydrogen evolution reaction.
[0093] Example 4 shows the performance test results of the electrolyte assembled into a battery. Figure 23 As shown in the figure, after 150 cycles, the coulombic efficiency reached 96.76%, the energy efficiency reached 72.80%, and the voltage efficiency reached 75.24%, which were 1.42%, 2.22%, and 1.21% higher than the blank control group, respectively.
[0094] Example 4 shows the capacity recovery curve of the battery assembled with the electrolyte as follows: Figure 24As shown in the figure, after 300 charge-discharge cycles, the capacity retention rate can reach 74.7%. At this time, the positive and negative electrolytes are fully mixed and then constant current charge-discharge test is performed. The discharge capacity can be restored to 94.8% of the initial discharge capacity.
[0095] The performance of the battery electrolyte obtained from the blank control group was tested according to the method in Example 1, and the electrolyte was assembled into a battery for performance testing. The results are as follows: Figures 25-29 The testing method is as described in Example 1.
[0096] Figure 25 The cyclic voltammetry curve of the positive electrode of the electrolyte is shown in the blank control group. Figure 26 The high-temperature positive electrode cyclic voltammetry test curve of the electrolyte obtained as a blank control group is shown. Figure 27 This is a SEM image of the negative electrode after testing the blank control group. Figure 28 The electrolyte assembly was used as a blank control group to obtain the battery performance test results. As can be seen from the figure, after 150 cycles, the coulombic efficiency reached 95.34%, the energy efficiency reached 70.58%, and the voltage efficiency reached 74.03%. Figure 29 The figure shows the capacity recovery curve of the blank control group battery. As can be seen from the figure, after 300 charge-discharge cycles, the capacity retention rate can reach 68.3%. At this time, the positive and negative electrolytes are fully mixed and then constant current charge-discharge test is performed. The discharge capacity can be restored to 90.1% of the initial discharge capacity.
[0097] The cycle efficiency results of the batteries in Examples 1-4 and the blank control group are shown in Table 1.
[0098] Table 1. Cycle efficiency of batteries in Examples 1-4 and the blank control group
[0099] The modified battery electrolyte provided by this invention plays a crucial role at both the positive and negative electrodes. On the negative electrode side, dissolved Bi... 3+ During charging, bismuth can be reduced in situ to metallic bismuth with highly catalytically active sites on the electrode surface. Under the influence of the flow field, metallic bismuth adheres to the electrode surface, significantly accelerating Vo. 3+ / V 2+ The redox reaction kinetics of the redox couple are analyzed to suppress the hydrogen evolution side reaction, thereby improving the charge-discharge efficiency and stability of the negative electrode. On the positive electrode side, the dissolved Bi... 3+ It can react with trace amounts of free Cl in the system - A stepwise complexation reaction occurs, forming [BiCl] n ] (3-n)+The stable complex significantly reduces the activity of free chloride ions and the electrochemical reaction kinetics rate, and increases the chloride ion oxidation and precipitation potential, thereby effectively suppressing the chlorine side reaction at high potentials at the positive electrode.
[0100] The stepwise complexation formula is as follows:
[0101] During battery operation and temperature rise, the complexing ability of bismuth chloride complexes weakens with increasing temperature, allowing for slow dissociation and release of some bound chloride ions. An appropriate increase in free chloride ions can effectively improve the solubility stability of vanadium ions in the electrolyte, suppressing the hydrolysis and precipitation of vanadium ions that easily occur in high-concentration vanadium electrolytes during temperature rise or long-term cycling. Stability constants of various complexes are also discussed. The expression is as follows:
[0102] Crucially, as battery cycle counts increase, battery capacity continuously decreases. This invention simultaneously applies bismuth-containing additives to both the positive and negative electrode electrolytes, ensuring the compatibility of the positive and negative electrode electrolyte systems. Therefore, when the battery undergoes capacity recovery, simply mixing the positive and negative electrode electrolytes achieves a rebalancing of electrolyte concentration and volume, demonstrating a significant advantage in efficient capacity recovery. In summary, bismuth-based compounds, as electrolyte additives, simultaneously achieve a triple effect: negative electrode electrocatalysis, positive electrode chlorine gas suppression, and high-temperature auxiliary stabilization of vanadium electrolytes. They exhibit excellent electrochemical performance and engineering application potential in mixed-acid-based vanadium redox flow battery electrolytes.
Claims
1. A mixed acid based all-vanadium redox flow battery electrolyte containing a bismuth-based additive, characterized in that, The desired modified battery electrolyte can be obtained by adding a bismuth-containing additive to the electrolyte of a mixed-acid-based vanadium redox flow battery and then electrolyzing it. The concentration of the bismuth-containing additive in the modified battery electrolyte is 0.01 mol / L – 0.1 mol / L; the bismuth-containing additive is one or more of bismuth sulfate, bismuth formate, bismuth citrate, and bismuth tartrate mixed in any proportion.
2. The mixed acid based vanadium redox flow battery electrolyte containing bismuth-based additive according to claim 1, characterized in that, The vanadium ions in the mixed acid-based vanadium redox flow battery electrolyte are tetravalent vanadium ions, with a concentration of 1.6 mol / L-2.5 mol / L.
3. The hybrid acid-based redox flow battery electrolyte with bismuth-based additive according to claim 1, characterized in that, The sulfate concentration in the mixed acid-based vanadium redox flow battery electrolyte is 3 mol / L-6 mol / L, and the chloride concentration in the modified battery electrolyte is 0.5 mol / L-2.5 mol / L.
4. The method of claim 1-3 for the preparation of a mixed acid based vanadium redox flow battery electrolyte containing bismuth-based additives, characterized in that, Includes the following steps: Step 1: Prepare a tetravalent vanadium oxysulfate solution; Step 2: Add the bismuth-containing additive and hydrochloric acid to the vanadium oxysulfate solution obtained in Step 1, stir thoroughly to react, and then electrolyze to obtain the desired modified battery electrolyte.
5. A process for the preparation of a mixed acid based redox flow battery electrolyte containing bismuth-based additives as claimed in claim 4, wherein, The method for preparing the tetravalent vanadium oxysulfate solution is as follows: Under oil bath conditions, adding oxalic acid to a sulfuric acid solution to reduce vanadium pentoxide yields a tetravalent vanadium oxysulfate solution.
6. A process for the preparation of a mixed acid based redox flow battery electrolyte containing a bismuth-based additive according to claim 5, characterized in that, The oil bath temperature is 60-80 ℃.
7. A process for the preparation of a mixed acid based redox flow battery electrolyte containing bismuth-based additives as claimed in claim 4, wherein, In step 2, the reaction temperature is 50-70 ℃ and the reaction time is 1-3 h.
8. Use of a mixed acid based vanadium flow battery electrolyte containing a bismuth-based additive, characterized in that, The modified battery electrolyte is obtained by any one of the preparation methods described in claims 4 to 7, and the modified battery electrolyte is used to assemble a mixed acid-based vanadium redox flow battery.
9. A mixed-acid-based all-vanadium redox flow battery containing bismuth-based additives, characterized in that, The battery is assembled using a modified battery electrolyte obtained by any one of the preparation methods described in claims 4 to 7 as the positive and negative electrode electrolytes.